An investigation on Jawi CAPTCHA based security for login authentication and authorization: Is it an alternative solution? - Sakinah Ali Pitchay; Madihah Mohd Saudi; Farida Hazwani Mohd Ridzuan; Nurlida Basir; Nur Fatin Nabila Mohd Rafei Heng; Mohd Suhaimi N.N. (Newswood Limited, 2024)
Index by Scopus